Oral manifestations of dengue fever: A rarity and literature review - Bhardwaj, Vinay Kumar; Negi, Nishant; Jhingta, Pravesh; Sharma, Deepak (European Journal of General Dentistry, 2016)
Dengue is a viral infection with fatal potential complications. It is also called break-bone fever. Worldwide, dengue infection is the most common mosquito-borne viral disease. It is caused by vector Aedes aegypti and represents a major public health issue in more than 100 tropical countries. This may be associated with a variety of mucocutaneous manifestations, which may be of help in early diagnosis. Dengue viral infections are characterized by abrupt febrile illness, but can also lead to significant morbidity and mortality. Hence, it requires an early and correct diagnosis. Gingival bleeding is the most common oral manifestation of dengue infections. Many biochemical assays and hematological investigations may aid in the further diagnosis and treatment of the fatal disease. Although oral lesions are uncommon in dengue infections and if occur, may be mistaken for platelet abnormality or hemorrhagic disorders. This review emphasizes the significance of oral lesions as it may be the early indicators of dengue hemorrhagic fever.
Keywords: Dengue fever; oral manifestations; platelet count